Bird survey to the Chesterfield islands on board patrolship La Moqueuse, 26 January - 01 February 2009 - Borsa, Philippe (HAL CCSD, 2009)
IRD, Noumea report A census of the birds of Ilot Loop and Ilots du Mouillage (Chesterfield Atoll, Coral Sea) was taken during a trip of patrolship La Moqueuse of the French Navy, from 26 January to 01 February 2009. Fourteen bird species were observed on the islets, including 10 seabirds breeding (Wedge-tailed Shearwater Ardenna pacifica, Masked Booby Sula dactylatra, Brown Booby S. leucogaster, Red-footed Booby S. sula, Lesser Frigatebird Fregata ariel, Pacific Frigatebird F. minor, Black Noddy Anous minutus, Brown Noddy A. stolidus, Crested Tern Thalasseus bergii and Sooty Tern Onychoprion fuscatus), 1 seabird apparently not breeding at the time of the visit (Black-naped Tern S. sumatrana), two shorebirds (Turnstone Arenaria interpres, Wandering Tattler Tringa incana) and the Buff-banded Rail Gallirallus philippensis. Wedge-tailed Shearwaters were abundant everywhere at sea, except inside the Chesterfield lagoon. Various observations suggest that the Chesterfield Islands is an important breeding site for the Green Turtle Chelonia mydas. Un recensement des oiseaux de l'îlot Loop et des îlots du Mouillage (atoll des Chesterfield, mer de Corail) a été fait à l'occasion d'une mission de surveillance du patrouilleur La Moqueuse de la Marine nationale, du 26 janvier au 1er février 2009. Quatorze espèces d'oiseaux ont été observées sur les îlots, dont dix oiseaux marins nicheurs (puffin fouquet Ardenna pacifica, noddi noir Anous minutus, noddi brun A. stolidus, sterne huppée Thalasseus bergii, sterne fuligineuse Onychoprion fuscatus, fou masqué Sula dactylatra, fou brun S. leucogaster, fou à pieds rouges S. sula, frégate ariel Fregata ariel, frégate du Pacifique F. minor), un oiseau marin apparemment non nicheur au moment de la mission (sterne à nuque noire S. sumatrana), deux limicoles (tournepierre Arenaria interpres et chevalier Tringa incana) et le râle à bandes Gallirallus philippensis. Le puffin fouquet était abondant en mer, dans le lagon sud-ouest de la grande terre et dans la mer de Corail, mais absent ...